2022
DOI: 10.36720/nhjk.v11i1.340
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Quality of Life Among Children With Thalassemia Major: A Literature Review

Abstract: Background: Thalassemia major is a chronic disease in children that harms children quality of life by interrupting physical function, emotional function, social function, and school function. Objectives: This study aims to identify factors contributed to quality of life among children with thalassemia major. Design: The research design used systematic review based on the PRISMA guideline. Data Sources: The source of the articles used three databases including Pubmed, Science Direct, and NCBI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…It is noteworthy that the age of diagnosis was an influential factor in HRQoL in our study. The enrolled patients who were diagnosed older than 2 years had significantly higher total HRQoL scores than those who were diagnosed younger, which is congruent with previous studies (19,(28)(29)(30)(31). It might be attributed to lesser duration of suffering.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is noteworthy that the age of diagnosis was an influential factor in HRQoL in our study. The enrolled patients who were diagnosed older than 2 years had significantly higher total HRQoL scores than those who were diagnosed younger, which is congruent with previous studies (19,(28)(29)(30)(31). It might be attributed to lesser duration of suffering.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies attributed the higher scores at younger ages to the recent onset of the disease, which led to less iron overload and thus fewer consequences (21,26). Additionally, as the patient matures, he becomes aware of the nature of his disease, undergoes more repeated blood transfusion visits, school absence, bullying at school, and obvious morphological changes result in poor self-esteem, expression of negative thoughts toward their chronic illness, leading to social withdrawal, and low social performance (27,28). Nevertheless, other studies contradicted our results and reported that age was not an effective factor in poor scoring in HRQol.…”
Section: Discussioncontrasting
confidence: 49%